PENGARUH TINGKAT PENDIDIKAN DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASAYRAKAT DI KABUPATEN/KOTA PROVINSI BALI - Septian, Muhammad Aji; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Poverty hit Indonesian economy, until now has greatly affected the welfare of the people. Indonesia is still unable to get out of the trap of low economic growth, even though economic growth is a condition for creating jobs and reducing poverty. The objectives of this study; 1) analyze the effect of the level of education, infrastructure and village funds simultaneously on poverty in districts / cities Bali Province, 2) analyze the influence of the level of education, infrastructure and funds villages have a partial effect on poverty in regencies / cities Bali Province. The research method used multiple linear. The data used secondary data obtained at BPS Bali Province. The results of this study 1) Level of education and infrastructure has a positive effect on economic growth in the Regency / City of Bali Province. 2) Level of education, infrastructure and economic growth have a positive effect on the welfare of the people in the Regency / City of Bali Province. 3) There is an indirect effect of the level of education and infrastructure on the welfare of the community through economic growth in the Regency / City of Bali Province. Keywords: education level, infrastructure, economic growth, community welfare